2015
DOI: 10.1111/ajsp.12097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of voice and similarity on procedural fairness and trust: A dual process model of public acceptance based on representatives’ participation

Abstract: In citizen participation, a few representatives of the total citizen population participate in discussions with authorities regarding public decisions and policies. The present study examines a dual process model in which the representatives’ voice and similarity of values facilitate public acceptance through procedural fairness and trust in representatives, respectively. The results of an experiment employing a scenario method, which included participants from Japan (n = 211) and the Netherlands (n = 200), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The effect of process control found in this study indicates the viability of the process-oriented account, where perceptions of procedural fairness can be enhanced by promoting process control, even when decision control cannot be increased. This result is consistent with recent the findings of Nonami, Hirose, Ohnuma, Midden, and Ohtomo (2015) 39 ) , who showed that enhancing process control by taking account of the opinions of residents plays an important role in fostering favorable perceptions of procedural fairness and public acceptance of policy. It was also found that trust in the sincerity of the government predicted perceived procedural fairness.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of process control found in this study indicates the viability of the process-oriented account, where perceptions of procedural fairness can be enhanced by promoting process control, even when decision control cannot be increased. This result is consistent with recent the findings of Nonami, Hirose, Ohnuma, Midden, and Ohtomo (2015) 39 ) , who showed that enhancing process control by taking account of the opinions of residents plays an important role in fostering favorable perceptions of procedural fairness and public acceptance of policy. It was also found that trust in the sincerity of the government predicted perceived procedural fairness.…”
Section: Discussionsupporting
confidence: 92%
“…The NIMBY issue 318 in the acceptance of a repository of designated waste may be evoked by the different 319 perceptions of fairness between residents in the possible siting areas and the non-siting repository have yet to be chosen. In the domain of justice research, the validity of studies 359 with hypothetical scenarios has been confirmed (Nonami et al 2015;van den Bos 1999).…”
mentioning
confidence: 96%
“…It is widely recognized that citizens should be accorded with opportunities to express their opinions and that diverse opinions should be reflected in the policy plan [30,33]. The opportunity to express opinions and the reflection of the opinions are lumped together as "reflection of voices", which is one of the most widely applied criteria in procedural fairness adjudications [34][35][36]. The inclusion of the voice entails the necessity of the involvement of citizens in the early stage of the planning; otherwise, it is difficult to reflect their opinions.…”
Section: Designing Hybrid Stepwise Participatory Programsmentioning
confidence: 99%